Shared heritability of human face and brain shape - Naqvi, Sahin (Nat Genet, 2021)
Evidence from model organisms and clinical genetics suggests coordination between the developing brain and face, but the role of this link in common genetic variation remains unknown. We performed a multivariate genome-wide association study (GWAS) of cortical surface morphology in 19,644 European-ancestry individuals, identifying 472 genomic loci influencing brain shape, of which 76 are also linked to facial shape. Shared loci include transcription factors involved in craniofacial development, as well as members of signaling pathways implicated in brain-face crosstalk. Brain shape heritability is equivalently enriched near regulatory regions active in either forebrain organoids or facial progenitors. However, we do not detect significant overlap between shared brain-face GWAS signals and variants affecting behavioral-cognitive traits. These results suggest that early in embryogenesis, the face and brain mutually shape each other through both structural effects and paracrine signaling, but this interplay may not impact later brain development associated with cognitive function.